Changes in Food Consumption During the COVID-19 Pandemic: Analysis of Consumer Survey Data From the First Lockdown Period in Denmark, Germany, and Slovenia - Janssen, Meike; Chang, Betty P. I.; Hristov, Hristo; Pravst, Igor; Profeta, Adriano; Millard, Jeremy (Frontiers in Nutrition, 2021)
This paper focuses on changes in food consumption that occurred during the COVID-19 pandemic. Its objective is to map changes at individual consumer level and identify the influence of different factors related to the COVID-19 pandemic on changes in individual food consumption. We conducted a cross-sectional online survey among 2,680 residents of Denmark (DK), Germany (DE) and Slovenia (SI) using quota sampling for gender, age and regional distribution. Data on consumption frequencies before and during the pandemic were collected with a food frequency questionnaire in the spring of 2020 (during the first lockdown period) for important types of fresh food and non-perishable food. Our results showed that, depending on the type of food, 15-42% of study participants changed their consumption frequency during the pandemic, compared to before. In all the study countries, the food categories with the highest rates of change were frozen food, canned food, and cake & biscuits; among the food categories with lower rates of change were bread, alcoholic drinks, and dairy products. People across all three countries shopped less frequently during lockdown and there was an overall reduction in the consumption of fresh foods, but an increase in the consumption of food with a longer shelf life in Denmark and Germany. Interestingly though, we observed diverging trends in all food categories analysed, with some people decreasing and others increasing their consumption frequencies, demonstrating that the pandemic had different impacts on people’s lifestyles and food consumption patterns. Using the method of multinomial regression analysis, we identified factors significantly (p<0.01, p<0.05, p<0.1) related to increases and decreases of individuals’ consumption frequencies in different food categories. The factors include restrictions put in place in response to the pandemic (i.e. closure of physical workplaces, canteens, cafés and restaurants, schools and childcare institutions), changes in households’ grocery shopping frequency, individuals’ perceived risk of COVID-19, income losses due to the pandemic, and socio-demographic factors. Interesting differences between the countries were detected, allowing insights into the different food cultures. Conclusions include implications for policy-makers and actors in the food supply chain on the issues of healthy diets, food system resilience, and behaviour change.